Issues regarding environmental protection in Romania - Draghicescu, Mirela (Studies and Scientific Researches. Economics Edition, 2010)
The “environmental protection” activity in our country should be approached by taking into consideration its entire complexity, and the most reliable solutions may be provided only by direct and permanent reference to the vast issue of social development in its entirety. The present work aims to draw attention towards pollution, the main cause of environmental deterioration in Romania, as well as towards the management of waste materials, while taking into account the national strategy. In Romania, environmental protection is a distinct domain of the national policy, establishing the priority objectives by “The National Strategy for Environmental Protection”, according to the communitarian strategy, as well as to the tendencies and initiatives existing at global level. Our country’s efforts over the past years with respect to environmental protection are very important in the framework of contemporary economy and are reflected in the expenses incurred for environmental protection.